1998
DOI: 10.1159/000017038
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Pathological Stages of Alzheimer’s Disease in Thin Paraffin Sections: A Comparative Study

Abstract: The staging method proposed by Braak and Braak allows the objective and reliable assessment of Alzheimer-related neurofibrillary pathology. Originally the method was designed for 100-µm thick sections. However, the use of thick sections proved to present difficulties in a routine neuropathology laboratory. In order to adapt the staging method for thin paraffin-embedded sections, we performed an inter- and intrarater study analysing the reliability of the staging method in thin sections. Statistical analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…We found that staging was largely independent of both the silver stain used to visualize NFT (Gallyas or modified Bielschowsky silver stains) and the level of the hippocampus examined. Previous studies [42,44] and our results suggest that the tangle staging protocol is highly reliable and reproducible and is independent of laboratory technique, similar to the CERAD protocol [40]. Our study shows that the same staining technique and block selection recommended by CERAD can be used for the simplified staging protocol with high interrater agreement.…”
Section: Commentsupporting
confidence: 71%
See 1 more Smart Citation
“…We found that staging was largely independent of both the silver stain used to visualize NFT (Gallyas or modified Bielschowsky silver stains) and the level of the hippocampus examined. Previous studies [42,44] and our results suggest that the tangle staging protocol is highly reliable and reproducible and is independent of laboratory technique, similar to the CERAD protocol [40]. Our study shows that the same staining technique and block selection recommended by CERAD can be used for the simplified staging protocol with high interrater agreement.…”
Section: Commentsupporting
confidence: 71%
“…The Braak staging protocol correlates with clinical indices of dementia [16,20] and, not unexpectedly, with the distribution and density of both neurofibrillary tangles (NFT) [2,4,15,16,29,37,41] and abnormally phosphorylated tau [29,41]. It is relatively simple to use (requiring neuropathological examination of only two blocks of tissue) and can reliably be applied to a wide range of tissue section thicknesses and embedding media [7,20,21,42,44]. However, because one of the tissue blocks is not routinely sampled and the recommended silver stain is not commonly used, the staging protocol is largely restricted to research settings.…”
Section: Introductionmentioning
confidence: 99%
“…NACC coordinates collection of phenotype data from the 29 ADCs, cleans all data, coordinates implementation of definitions of AD cases and controls, and coordinates collection of samples. The ADC cohort consists of 2,499 autopsy-confirmed and 1,748 clinically-confirmed AD cases, and 175 cognitively normal elders (CNEs) with complete neuropathology data who were older than 60 years at age of death, and 2,669 living CNEs evaluated using the Uniform dataset (UDS) protocol 43,44 who were documented to not have mild cognitive impairment (MCI) and were between 60 and 100 years of age at assessment. Among cases, the average age at onset was 71.6 years (±9.0 years), and APOE genotypes were 0.1% e22, 3.5% e23, 31.6% e33, 2.8% e24, 44.3% e34, and 14.7% e44.…”
Section: Methodsmentioning
confidence: 99%
“…Alzheimer's disease pathology was assessed according to the CERAD19 and modified Braak protocols 20. A 10 point cortical Lewy body score was derived from assessments of five sections (anterior cingulate gyrus, parahippocampal gyrus, insular, middle frontal, middle temporal, and visual association cortex stained for ubiquitin) using the consensus guidelines17 with two variations.…”
Section: Methodsmentioning
confidence: 99%